Integrated cage-cum-pond culture system with walking catfish (Clarias batrachus) in cages and tilapia (Oreochromis niloticus) in open ponds - Sangma, Phanindra; Wahab, Md Abdul; Haque, Shahroz Mahean; Mondal, Sanjib Kumar (Research in Agriculture Livestock and Fisheries, 2017)
An experiment was conducted for a period of 97 days at the Fisheries Field Laboratory Complex, Bangladesh Agricultural University, Mymensingh to determine the potential of the cage-cum-pond culture of walking catfish, as well as to assess the economic and environmental benefits of this system. The experiment had two treatments in triplicate. One treatment comprised walking catfish in cage and tilapia in open pond, and the other treatment comprised both walking catfish and tilapia stocked together in open ponds. Ponds of both treatments were stocked with walking catfish and tilapia at a stocking density of 10,000 and 20,000 ha-1, respectively. Fishes in both treatments were fed with commercial pelleted feed (26% crude protein) twice daily at the rate of 10% body weight of walking catfish. All ponds were fertilized with urea and TSP at a rate of 50 kgha-1 bi-weekly. Survival of catfish was very low in both treatments ranging from 8.33 to 21.33%. Specific growth rate of catfish was significantly higher (P<0.021) in treatment-2 than in treatment-1 with a value of 2.42 and 1.69 g fish-1d-1, respectively. The net yield for catfish of treatment-1 and 2 were 49.67 and 43.45 kgha-1, respectively and there was no significant difference between the treatments. The survival rate of tilapia was 65.17 and 71.17% with daily weight gain of 2.31 and 2.22g fish-1 in treatment-1 and 2, respectively. Net yield were 817.00 and 790.63 kg ha-1, respectively and there were no significant difference in net yield of tilapia between treatments. Net profit obtained from integrated-cage-cum pond culture (Tk. 24,518 ha-197d-1) was higher than that of open pond (Tk 22,685 ha-197d-1). Res. Agric. Livest. Fish.4(3): 221-227, December 2017